Hyperfine structure and isotope shifts in 461.9 nm forbidden line of Pb I - Wąsowicz, Tomasz J.; Drozdowski, Ryszard; Kwela, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Studies of the hyperfine structure and the isotope shifts in the 461.9 nm (1S0–3P1) magnetic-dipole line of Pb I are presented. As a light source the electrodeless discharge tube was used. The high resolution spectral apparatus consisted of a silver coated Fabry–Perot etalon and a grating spectrograph combined with a CCD camera used as a detector. In the analysis of the spectra a computer simulation technique was used. The experiments with the isotope 207Pb yielded the hyperfine structure splitting constant A for the 3P1 level of the 6s26p2 ground configuration. In the experiment with natural lead the isotope shifts between four stable isotopes (204, 206, 207, 208) were measured.
Optica Applicata, Vol. 36, 2006, nr 4, s. 529-533
Keywords: optyka; hyperfine structure; isotope shift; forbidden lines; lead